Comparison of drying kinetics, energy efficiency and color of dried eggplant slices with two different configurations of a heat pump dryer - Doymaz, Ibrahim; Tunckal, Cuneyt; Goksel, Zekiye (TAYLOR & FRANCIS INC, 2023)
In this study, Kemer eggplants (Solanum melongena L.) were examined in terms of system performance and energy efficiency after drying at constant air temperature and different operating systems developed on a heat pump dryer. The air velocity and the drying time have a negative correlation was observed. In addition, the Midilli & Kucuk model was the most appropriate model to explain the experimental data of dried eggplant samples obtained from this study. Effective moisture diffusivity was calculated between 6.08 x 10(-10) and 7.30 x 10(-10) m(2)/s depending on air velocity values. The reduction of the eggplant slices from 12.158 (g water/g dry matter (dm)) moisture value to 0.645 (g water/g dm) moisture value took 236 min at 1 m/s air velocity with the application of Serial Condenser and Parallel Evaporator Drying System (SCPEDS). The Serial Condenser Drying System (SCDS) was found to yield both the highest average condenser capacity with 2.256 kW and the highest system performance coefficient with 3.181. The brightness values (L) of dried eggplant samples increased compared to the fresh eggplant samples. The closest brightness value to the fresh samples was determined as 84.7 in the drying experiments with the air velocity of 0.5 m/s and the SCPEDS system. The other color parameters (b, C and h degrees) decreased during drying. The highest total color change value (8.05) was obtained with SCPEDS system at 1.0 m/s. The highest browning index value (63.48) was reached in the drying experiments performed with the SCDS system at 0.75 m/s.
Keywords: Drying system; eggplant; effective moisture diffusivity; energy efficiency; mathematical modeling; PERFORMANCE ANALYSIS; ANTIOXIDANT CAPACITY; TEMPERATURE; Energy & Fuels; Engineering; Environmental Sciences & Ecology